Fungi applications and management strategies - Deshmukh, S. K. (Sunil K.); Misra, J. K.; Tewari, J. P.; Papp, Tamas (Boca Raton, FL CRC Press, an imprint of the Taylor & Francis Group, 2016)
"The book deals with the application of fungi and the strategic management of some plant pathogens. It covers fungal bioactive metabolites, with emphasis on those secondary metabolites that are produced by various endophytes, their pharmaceutical and agricultural uses, regulation of the metabolites, mycotoxins, nutritional value of mushrooms, prospecting of thermophilic and wood-rotting fungi, and fungi as myconano factories. Strategies for the management of some plant pathogenic fungi of rice and soybean have also been dealt with. Updated information for all these aspects has been presented and discussed in different chapters."
"A Science Publishers book"
Includes bibliographical references and index.
Keywords: Fungi